2019
DOI: 10.3390/polym11081234
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability, Fire and Smoke Behaviour of Epoxy Composites Modified with Plant Waste Fillers

Abstract: The influence of plant fillers on the flammability and smoke emission of natural composites was investigated. Epoxy composites with 15, 25, and 35 wt % of walnut and hazelnut shell, as well as sunflower husk, were prepared and examined. The ground organic components were characterized by grain size distribution, thermogravimetric analysis (TGA) and microstructure observations (SEM). The composite materials were subjected to dynamic mechanical analysis (DMA) and structural evaluation with scanning electron micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 40 publications
1
26
0
1
Order By: Relevance
“…There have been many literature reports about modification of epoxy resin using various types of bio-based materials, for examples, clay [5], lignin [6], plant seed oils [7], Eugenol [8], vanillin [9], plant waste filler [10], cellulose nanofibrils [11] and others. The use of natural materials (mainly bio-phenolic types) in epoxy technologies providing similar properties to those of synthetics materials such as modulus, curing and mechanical strength is still a highly important challenge.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many literature reports about modification of epoxy resin using various types of bio-based materials, for examples, clay [5], lignin [6], plant seed oils [7], Eugenol [8], vanillin [9], plant waste filler [10], cellulose nanofibrils [11] and others. The use of natural materials (mainly bio-phenolic types) in epoxy technologies providing similar properties to those of synthetics materials such as modulus, curing and mechanical strength is still a highly important challenge.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the MAHRE during the cone calorimetry test allows to evaluate the fire behavior of a material in full‐scale conditions. [ 42 ] The composites show MARHE values notably higher than in the case of pure PLA. However, once again, no correlation between the oil content and the cone calorimetry test results can be noticed in this case.…”
Section: Resultsmentioning
confidence: 94%
“…For comparison, El‐Ghazawy et al [ 25 ] reported the thermal behavior of commercial epoxy resin (DGEBA) and rosin‐based epoxy resin (TGK) isothermally cured with a p‐phenyl diamine, a commercial crosslinker, that exhibited IDT at 255°C and 260°C, respectively, and T max at 312°C and 287°C, respectively. Salasinska et al [ 38 ] have also reported thermal analysis of commercial bisphenol A‐based epoxy resin cured with isophorone diamine crosslinker. The epoxy system showed 5% and 10% weight loss at 172°C and 224°C for the resin system.…”
Section: Resultsmentioning
confidence: 99%